2020
DOI: 10.1371/journal.pone.0222259
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarkers and overall survival in patients with advanced hepatocellular carcinoma treated with TGF-βRI inhibitor galunisertib

Abstract: Background Transforming growth factor beta (TGF-β) signalling is involved in the development of hepatocellular carcinoma (HCC). We followed changes in biomarkers during treatment of patients with HCC with the TGF-βRI/ALK5 inhibitor galunisertib. Methods This phase 2 study (NCT01246986) enrolled second-line patients with advanced HCC into one of two cohorts of baseline serum alpha-fetoprotein (AFP): Part A (AFP �1.5x ULN) or Part B (AFP <1.5x ULN). Baseline and postbaseline levels of AFP, TGF-β1, E-cadherin, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…In the present study, we observed that low values of serum ERBB3 resulted associated with longer OS; interestingly, the association remained significant even after adjustment for patients’ age, liver function, and tumor stage (HR = 2.24, p = 0.017). Similarly, Giannelli and colleagues previously showed that higher baseline plasma ERBB3 levels were significantly associated with poor survival (HR = 2.21, p < 0.001) in patients with advanced HCC [ 19 ].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the present study, we observed that low values of serum ERBB3 resulted associated with longer OS; interestingly, the association remained significant even after adjustment for patients’ age, liver function, and tumor stage (HR = 2.24, p = 0.017). Similarly, Giannelli and colleagues previously showed that higher baseline plasma ERBB3 levels were significantly associated with poor survival (HR = 2.21, p < 0.001) in patients with advanced HCC [ 19 ].…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, increasing evidence supports the involvement of ERBB receptors, together with the process of epithelial–mesenchymal transition, in the development and progression of different types of human cancer [ 14 , 15 , 16 , 17 ]. Recent studies suggested that secreted ERBB3 isoforms were able to discriminate between patients with or without HCC [ 18 ], and that serum ERBB3 was associated with overall survival (OS) in patients with advanced HCC [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior data suggest that baseline circulating plasma AFP and TGF-β1, AFP and TGF-β1 response kinetics, and tumor SMAD complex activity might discriminate a sensitive HCC subset. 30 Although AFP and TGF-β1 were sampled over treatment on our study, the small sample size limits any definitive conclusion regarding the prognostic value of baseline plasma levels, or the predictive value of AFP or TGF-β1 response. Furthermore, as pretreatment biopsy was not mandated due to safety considerations related to using an antiangiogenic, activity of the TGFβ axis at the tumor level could not be assessed.…”
Section: Discussionmentioning
confidence: 96%
“… 5 Since then, numerous clinical trials on MKIs of VEGFR have yielded positive results, leading to the approval of lenvatinib 6 as first-line treatment and cabozantinib 7 and ramucirumab 8 as subsequent-line treatments. In addition, there are many promising molecularly targeted agents currently being studied in clinical trials, such as transforming growth factor beta (TGF-β) inhibitors, 9 , 10 MET inhibitors, 11 fibroblast growth factor receptor 4 (FGFR4) inhibitors, 12 and other similar molecular inhibitors.…”
Section: Introductionmentioning
confidence: 99%